A economia comportamental da saúde : contribuições para a análise do problema da obesidade no Brasil e no mundo do século XXI - Ferrari, Felipe Galves (2019)
The main objective of this essay is to analyze the obesity, a rapid growing health problem that brings within costs for the well-being of the economic agents and for the market in general. By comparing, two research lines, the first one the traditional health economics that take as premise the neoclassical theory, followed by the behavioral health economics. It would be possible to compare how the different theories explain the problem and how they can address the question for solving it. This study will only be possible with a large literature review, including comparing some application cases of interventions.